Relationships in the family and their impact on the degree of the Internet addiction among school youth - Barbara Niedorys; Monika Mikos; Marcin Stanisław Rząca; Katarzyna Kocka (Kazimierz Wielki University, 2018)
Introduction: Family relationships have a huge influence on the personality of a teenager, his future elections, personal and professional development. If the basic emotional needs of family members are not satisfying, there are no family ties between them and the parents' attitude towards the child are inadequate it may lead to impaired proper development of a young person's identity and development of risky behaviors including the Internet addiction, which is particularly dangerous. Aim: Determining the impact of family relationships on the level of the Internet addiction among school youth. Material and methods: The study covered 263 junior high school students and high school students. The research was carried out from November to December 2017 in schools in Lublin, Łaszczów and Nabróż. Some of the results were also collected via the Internet. The applied research method was a diagnostic survey , and tools: the Kimberly Young' Internet Addiction Test and the authors' self-designed survey. Results: The Internet addiction was observed in 11% and the risk of addiction in 7% of the surveyed students. Every fifth student addicted to the Internet (21%) grew up in an incomplete family. Repeated conflicts with parents were more frequent among students at risk of addiction (47%) and those addicted to the Internet (46%) than among school youth who were not addicted to the Internet (25%). Students addicted to the Internet more often felt misunderstood (51%) and unaccepted (25%) by their families in contrast to other respondents. Nearly every second person at risk of addiction (47%) and the Internet-addicted (43%) admits that its parents rarely pay attention to the amount of time spent on the Internet by their child. Conclusions: • Conflicts between parents / carers and school youth are more frequent in the group of respondents addicted to the Internet or at risk of this addiction. • Misunderstandings and lack of acceptance from the family more often accompanied the Internet-addicted school youth. • Parents of students addicted to the Internet or at risk of this addiction do not pay enough attention to the amount of time spent on the Internet by their child.